EFFECT OF “PANAROOT-98” ON THE CLINICAL AND PHYSIOLOGICAL CONDITION OF OSTRICH - Shakhlo Aliyevna, Babaeva (Research Parks Publishing LLC, 2022)
The article describes the effectiveness and influence of the drug